Mathematics compared to other disciplines in the citation Scimago index (2017)
This article presents the production of mathematics discipline from the first five journals, in terms of subjects, under the index Scimago (April 15, 2017); titles and abstracts from the sample mentioned are classified and compared. Then, we compare the first 50 journals in mathematics with the first 50 in the discipline of education and in the same way the first 50 in the discipline of economics, this comparison is made around the participation of the country of the authors. Finally, we carry out an analysis (from scientometrics) of the Latin America mathematics journals from the index.